Penyusunan Dokumen Manajemen Risiko untuk Mendukung Pokdarwis Danau Kali Baru sebagai Rintisan Destinasi Wisata Berkelanjutan di Kota Bekasi - Dyah Mustika Wardani; Lilik Edi Saputro; Nova Yudha Andriansyah Putra; Gilang Fahreza (Lembaga Pengembangan Kinerja Dosen, 2026)
Kali Baru Lake is a community-based pilot tourism destination in Bekasi City managed by the Kali Baru Tourism Awareness Group (Pokdarwis Danau Indah Kalibaru). Preliminary observations indicate that destination management still faces limited human resource capacity, inadequate safety facilities, and the absence of a structured risk management document as a governance instrument. This community service program aims to strengthen the institutional capacity of the Pokdarwis through assistance in developing a risk management document, tourism safety training, formulation of operational standard operating procedures (SOPs), and enhancement of risk communication. The implementation method applied a participatory approach consisting of initial assessment, training, document development workshops, implementation of safety-supporting facilities, and evaluation. The results show the completion of a risk management document based on hazard identification and mitigation, the establishment of several safety and operational SOPs, the availability of risk communication media, and improved knowledge and skills of Pokdarwis members in managing sustainable tourism destinations. This program contributes to strengthening destination governance professionalism, enhancing tourism safety, and improving the readiness of Kali Baru Lake as a safe and sustainable community-based tourism destination.